2008
DOI: 10.1021/nl801059v
|View full text |Cite
|
Sign up to set email alerts
|

Conductance of p-n-p Graphene Structures with “Air-Bridge” Top Gates

Abstract: We have fabricated graphene devices with a top gate separated from the graphene layer by an air gap-a design which does not decrease the mobility of charge carriers under the gate. This gate is used to realise p-n-p structures where the conducting properties of chiral carriers are studied. The band profile of the structures is calculated taking into account the specifics of the graphene density of states and is used to find the resistance of the p-n junctions expected for chiral carriers. We show that ballisti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

19
215
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(236 citation statements)
references
References 18 publications
19
215
1
1
Order By: Relevance
“…In recent years, there has been a vivid discussion on the issue of transport through bipolar junctions giving rise to some thought provoking theoretical approaches [8][9][10][11] and experiments [12][13][14]. Consequently, different intriguing situations such as Klein tunneling and collimation at a single p-n junction or transmission through a bipolar barrier in the ballistic regime have been covered in scientific publications and revealed resonant behavior of conductance in analogy to optical Fabry-Pérot (FP) cavities [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been a vivid discussion on the issue of transport through bipolar junctions giving rise to some thought provoking theoretical approaches [8][9][10][11] and experiments [12][13][14]. Consequently, different intriguing situations such as Klein tunneling and collimation at a single p-n junction or transmission through a bipolar barrier in the ballistic regime have been covered in scientific publications and revealed resonant behavior of conductance in analogy to optical Fabry-Pérot (FP) cavities [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that it is possible to confine graphene electrons by electrostatic potentials [16][17][18][19][20][21][22][23][24][25][26][27][28], magnetic barriers [29][30][31][32][33][34][35][36][37][38][39], and straininduced fields [40][41][42][43]. Transmission through symmetric [15][16][17][18]27,28,32,[44][45][46][47][48][49][50][51][52][53][54][55][56] and asymmetric electrostatic barriers [25] have been studied and fully confined modes within a smooth one-dimensional potential have been predicted to exist at zero energy …”
Section: Introductionmentioning
confidence: 99%
“…One prime example is the Klein tunneling, perfect transmission through the barrier regardless of its width and energy height [5,[9][10][11][12][13][14][15][16][17][18][19]. Different from monolayer graphene, charge carriers in bilayer graphene (BLG) are massive Dirac fermions also with a chiral nature, but a finite density of states at zero energy [5,9,20,21].…”
mentioning
confidence: 99%
“…In a more sophisticated way, the bipolar regime, where the polarity of graphene regions controlled by the back gate and the top gate are different, can offer an opportunity to unravel crucial role of chirality in transport through the potential barrier [13,14,[16][17][18]. As shown in Fig.…”
mentioning
confidence: 99%